1982
DOI: 10.1113/jphysiol.1982.sp014197
|View full text |Cite
|
Sign up to set email alerts
|

Response properties of rat olfactory bulb neurones

Abstract: SUMMARY1. Response properties of rat olfactory bulb neurones were studied by recording single-unit activity evoked by stimuli delivered by an air-dilution olfactometer. Neural responses were quantified as peristimulus time histograms by averaging the responses evoked by eight presentations of the same stimulus. Animals were stimulated by means of controlled artificial sniffs produced by a vacuum source connected to the choana. 4 2. Evoked activity was divided into on-and after-responses. Three types of on-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 20 publications
(24 reference statements)
2
25
0
Order By: Relevance
“…Antidromic activation of axons in the lateral olfactory tract (LOT) can identify neurons that project from the MOB, but in many previous studies data from mitral and tufted cells were combined, and the cells were referred to as ‘mitral/tufted’ or ‘M/T’ cells (e.g., Buonviso et al, 1992; Imamura et al, 1992; Yokoi et al, 1995). In other prior studies (e.g., Mair, 1982; Chaput & Holley, 1980), cells were identified by depth in the MOB, but without antidromic activation. Such cells could be mitral cells, granule cells, or deep tufted cells.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Antidromic activation of axons in the lateral olfactory tract (LOT) can identify neurons that project from the MOB, but in many previous studies data from mitral and tufted cells were combined, and the cells were referred to as ‘mitral/tufted’ or ‘M/T’ cells (e.g., Buonviso et al, 1992; Imamura et al, 1992; Yokoi et al, 1995). In other prior studies (e.g., Mair, 1982; Chaput & Holley, 1980), cells were identified by depth in the MOB, but without antidromic activation. Such cells could be mitral cells, granule cells, or deep tufted cells.…”
Section: Discussionmentioning
confidence: 62%
“…Possibly the temporal pattern (bursting) or anatomical differences such as the extent of lateral dendrites or specific interactions with inhibitory interneurons in the glomerular or external plexiform layers are more important in coding odor information. Measurements of mitral cell responses to odor stimulation has revealed that some cells are excited while others are inhibited (e.g., Wellis et al, 1989; Nagayama et al, 2004), that the response can depend on odor concentration (e.g., Mair, 1982; Harrison & Scott, 1986, but also Chalansonnet & Chaput, 1998), and that responses in some cells are modulated by respiration (Macrides & Chorover, 1972; Chaput & Holley, 1980; Chaput et al, 1992; Buonviso et al, 2006). This range of response characteristics and their underlying neural circuits could form a more coherent pattern when more is known about the physiological subclasses of mitral cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of the spatial code being transformed into a temporal code for olfactory information also has been raised many times, based on observations that the temporal pattern of activity of mitral cells differs for different odorants, potentially allowing such differences to carry the coded odorant information (Kauer, 1974;Mair, 1982;Meredith, 1986;Harrison and Scott, 1986). In addition to temporal patterns of spiking in individual mitral cells, widespread odorant-evoked oscillatory patterns of a variety of periodicities also have been demonstrated in various olfactory systems (Adrian, 1950b;Freeman and Skarda, 1985;Freeman and Viana Di Prisco, 1986;Laurent and Naraghi, 1994;Gelperin, 1999;Kay, 2003).…”
Section: Temporal Coding Of Odorant Informationmentioning
confidence: 99%
“…Respiratory modulation of electro-encephalographic (EEG) and local field potential (LFP) signals has been extensively described in OB and OC (Boudreau & Freeman, 1963;Freeman, 1975;Freeman & Schneider, 1982;Freeman, 1983;Buonviso et al, 2003, Fontanini et al, 2003. Such a respiratory modulation has also been described in cell unitary activities in the OB mitral/tufted (Walsh, 1956;Macrides & Chorover, 1972;Chaput & Holley, 1980;Onoda & Mori, 1980;Mair, 1982;Pager, 1985;Chaput, 1986) and was recently described in the piriform cortex (PC) (Wilson, 1998;Litaudon et al, 2003). Rather than a variation in overall firing frequency, odor-evoked cell responses have often been reported as a temporal reorganization of their discharges into inhalation-related bursts of spikes.…”
Section: Introductionmentioning
confidence: 99%